Political economy of the environment in Turkey: gold mining conflict in Ida Mountain - Avcı, Duygu. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
This study analyzes the recent environmental conflict over permission to gold mining in close vicinity of Ida Mountain in Biga Peninsula, Turkey. Based on a field study conducted in the region, the factors that affect the positions of stakeholders visà- vis gold mining in Biga Peninsula are examined. Through in-depth interviews and focus group discussions, concerns, perceptions and expectations of stakeholders are elicited. On the basis of the insights from qualitative research, a questionnaire is administered to 738 citizens of the region to discover their positions. An econometric analysis is then performed to identify the factors that account for the differences in local public’s positions. The research findings suggest that material interests, values and perceptions regarding the environment underlie the conflicting positions of the stakeholders.
Keywords: Environmental policy -- Cost effectiveness.